Design and Characterization of Line-Waves Waveguides for Microwave Applications - Alessio Monti; Stefano Vellucci; Mirko Barbuto; Valentina Verri; Francesco Verni; Claudio Massagrande; Davide Ramaccia; Michela Longhi; Zahra Hamzavi-Zarghani; Luca Stefanini; Alessandro Toscano; Filiberto Bilotti (IEEE Open Journal of Antennas and Propagation)
Line-waves are one-dimensional modes propagating at the interface between two planar complementary surfaces, characterized by tight transversal confinement of the field. Despite their unique guiding properties, their use in real microwave devices is still in the early stages, lacking a comprehensive design procedure and comparative analysis with conventional guiding structures. To fill this gap, here we report a simple and straightforward workflow for designing waveguides supporting 1D modes propagation. The design is based on the analytical relations existing between the surface impedance of the propagating modes and the sheet impedance of the metasurfaces, which allow quick retrieval of the geometrical parameters of the complementary metasurfaces sustaining the line-wave propagation. This approach is used to design several waveguiding layouts and compare their transmission performance through full-wave simulations accounting for dielectric and ohmic losses. Finally, experimental results for some selected designs in the microwave regime are provided, and a thoughtful comparison between a line-wave waveguide and an equivalent microstrip transmission line is carried out to assess the suitability of these devices for efficient high-frequency waveguiding.